New compounds with anti-inflammatory potential from Disporum cantoniense. (December 2017) - Li, Zhifeng; Zhao, Huiling; Ouyang, Hui; Wang, Qi; Chen, Jie; Feng, Yulin; Yang, Shilin
Graphical abstract: Highlights: Two new compounds were isolated from Disporum cantoniense. Their structures were determined by various spectroscopic techniques. The absolute configurations of compounds were determined by ECD calculations analysis. They showed potent nitric oxide (NO) release in LPS-induced RAW264.7 macrophages. Abstract: Phytochemical investigation of Disporum cantoniense has resulted in the isolation of two new compounds, namely (3S, 4S, 5S)-5-C-(4-hydroxy-3-methoxybenzyl)-γ-lactone-2-deoxy-pentonic acid(1) and (3R, 4S, 5R)-5-C-(4-hydroxy-3-methoxybenzyl) -γ-lactone-2-deoxy-pentonic acid(2). Their structures were elucidated by various spectroscopic techniques. The absolute configurations of compounds were determined by ECD calculations analysis. Compound1 showed significant inhibition of nitric oxide (NO) release in LPS-induced RAW264.7 macrophages with the IC50 value of 6.43 ± 0.68 μM, comparable to that of positive control amino guanidine (9.14 ± 0.62 μM). Herein we report the isolation, structure elucidation, as well as the evaluation of the anti-inflammatory activities of these two compounds.